2016
DOI: 10.15744/2455-7641.2.102
|View full text |Cite
|
Sign up to set email alerts
|

T2* MRI Correlates with R2 Liver Iron Concentration in Transfusion Dependent Thalassaemia

Abstract: Research ArticleOpen Access Regular transfusion in thalassaemia major results in progressive iron overload and its complications. Chelation therapy can prevent these complications and has been pivotal in the improved survival of these patients. With inadequate chelation, cardiac arrhythmias and cardiomyopathy are the predominant causes of death, while endocrinopathies and cirrhosis contribute to both morbidity and mortality [1][2][3]. Each chelating agent has potential risks and benefits. The accurate assessme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
(16 reference statements)
1
0
0
Order By: Relevance
“…Our study showed highly negative significant correlation between R2* and T2* this is in agreement with Kidson-Gerber et al, [28] reported that a linear relationship between T2* and R2* with a correlation coefficient ( r) of 0.946, p<0.001.…”
Section: Discussionsupporting
confidence: 93%
“…Our study showed highly negative significant correlation between R2* and T2* this is in agreement with Kidson-Gerber et al, [28] reported that a linear relationship between T2* and R2* with a correlation coefficient ( r) of 0.946, p<0.001.…”
Section: Discussionsupporting
confidence: 93%